Nutrition and elite young athletes - Jeukendrup, A.; Cronin, L. (The Elite young athlete, 2011)
Nutrition can play an essential role in the health of elite young athletes as well as exercise performance. Children and adolescents need adequate energy intake to ensure proper growth, development, and maturation. In addition, the requirements may further increase with increasing exercise training. There are, however, several metabolic differences that result in slightly different advice for young versus adult athletes. For example, younger athletes generally rely more on fat as a fuel, have smaller glycogen stores and have a limited glycolytic capacity. This would imply reduced carbohydrate requirements but a greater capacity to oxidize fat. There are also differences in thermoregulation, although the exact impact on fluid requirements is not clear. The limited evidence suggests that acute energy and fluid imbalances can be detrimental to performance and there may be benefits of ingesting carbohydrate and fluid during exercise, especially during more prolonged exercise. Exogenous carbohydrate oxidation rates have been reported to contribute more to energy expenditure in children. This may, however, simply be a reflection of the fact that the oxidation of this carbohydrate is not limited by body size, but by absorption. Absorption rates are likely to be similar in children and adults and therefore exogenous carbohydrate oxidation rates should be comparable. The relative contribution will therefore be higher because of the lower absolute intensities in children. There are a large number of questions still unanswered and sports nutrition advice to the elite young athlete is largely extrapolated from the adult population. Therefore, more research is needed in the years to come to give better advice to these young athletes